2007
DOI: 10.1016/j.respol.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cognitive distance and absorptive capacity

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
201
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,085 publications
(257 citation statements)
references
References 71 publications
8
201
0
9
Order By: Relevance
“…Meyer-Krahmer 1985, Arndt-Sternberg 2000, Bathelt et al 2004) as well as cognitively proximate and distant partners (cf. Fritsch 2003, Nooteboom et al 2007, Balland et al 2013). Especially, the economic relevance of the type of partner (in terms of the proximity dimensions) has been the focus of researchers.…”
Section: Proximity Network and Innovationmentioning
confidence: 99%
See 3 more Smart Citations
“…Meyer-Krahmer 1985, Arndt-Sternberg 2000, Bathelt et al 2004) as well as cognitively proximate and distant partners (cf. Fritsch 2003, Nooteboom et al 2007, Balland et al 2013). Especially, the economic relevance of the type of partner (in terms of the proximity dimensions) has been the focus of researchers.…”
Section: Proximity Network and Innovationmentioning
confidence: 99%
“…Phelps (2010) found that access to greater variety improves innovation activities. Nooteboom et al (2007) and Broekel & Boschma (2012) provided evidence that, in terms of innovative success, an optimal level of cognitive proximity might exist. That is, both higher cognitive proximity (greater technological similarity) and lower cognitive proximity (lower technological similarity) tend to reduce the innovation performance of firms.…”
Section: Proximity Network and Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…This may depend on, among other things, the degree of proximity between the networks partners. While a high degree of any form of proximity might be considered a prerequisite to make agents interact, proximity between agents does not necessarily increase their innovative performance, and may possibly even harm it (Grabher and Stark, 1997;Boschma, 2005;Cantner and Meder, 2007;Nooteboom et al, 2007;Broekel and Meder, 2008). This is in line with what Gilsing et al (2007) found when they assessed the impact of technological distance in high-tech alliance networks on the innovative performance of the partner firms.…”
Section: Part 3 Network Evolution and Geographymentioning
confidence: 99%